Robert Todd Lincoln family papers - Lincoln, Robert Todd, 1843-1926.; Lincoln, Abraham, 1809-1865.; Lincoln, Mary Todd, 1818-1882.
Correspondence, legal and financial records, commissions, an autobiographical sketch, printed volumes, receipts, newspaper clippings, house plans, photographs, and a manuscript relating to Robert Todd Lincoln and his family. Includes material concerning houses in Georgetown (Washington, D.C.) and Manchester, Vt. Receipts include those with the name Grace Lincoln Temple, a noted interior decorator of the time. Includes Mary Todd Lincoln's correspondence during her confinement at the private sanitorium of Bellevue, in Batavia, Ill., and following her release in 1876. Correspondents in the Mary Todd Lincoln material include James B. Bradwell, Myra Bradwell, Elizabeth Todd Edwards, Richard J. Patterson, and Robert Todd Lincoln.
Family members represented include Robert Todd Lincoln (U.S. Army officer, U.S.secretary of war, diplomat, and lawyer), his wife Mary Harlan Lincoln, his daughters Mary Lincoln Isham and Jessie Lincoln Beckwith Johnson Randolph, his mother Mary Todd Lincoln, and his father Abraham Lincoln.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bradwell, James B. -- 1828-1907 -- Correspondence; Bradwell, Myra, -- 1831-1894 -- Correspondence; Edwards, Elizabeth Todd, -- 1813-1888 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Isham, Mary Lincoln, -- 1869-1938.; Lincoln, Mary Harlan, -- 1846-1937.; Patterson, Richard J. -- Correspondence; Randolph, Jessie Lincoln Beckwith Johnson, -- 1875-1948.; Temple, Grace Lincoln; Lincoln family; Architecture, Domestic -- Washington (D.C.); Architecture, Domestic -- Vermont -- Manchester; Asylums -- Illinois -- Batavia; Army officers; Cabinet officers; Diplomats; Lawyers